TOXINZ, the New Zealand Internet poisons information database: The first decade. (8th May 2016) - Fountain, John S; Slaughter, Robin J
Abstract: Objective: The New Zealand National Poisons Centre has, over a number of years, developed an electronic poisons information database. In 2002, this was released astoxin z ™ (University of Otago, Dunedin, New Zealand), an Internet accessible version. The objective of this study is to describe New Zealand subscriber utilisation of TOXINZ with an emphasis on pharmaceutical monographs viewed. Methods: A retrospective review was conducted of records of New Zealand subscriber access to TOXINZ monographs during the period 1 January 2003 to 31 December 2012. Telephone enquiry data to the New Zealand National Poisons Centre was also obtained for the same time period. Results: Over the decade, 201 255 TOXINZ monographs were accessed, with annual numbers of documents viewed doubling from 13 718 in 2003 to 28 782 in 2012. Pharmaceuticals were the largest group viewed with 132 316 documents accessed (65.7% of all documents), followed by monographs relating to chemicals 46 061 (22.9%), substances of abuse 6698 (3.3%), plants 6563 (3.3%), supportive care 4668 (2.3%), animals 2553 (1.3%), and other 2396 (1.2%). In regard to the pharmaceuticals, high or rapidly increasing levels of enquiries were identified for venlafaxine, quetiapine, paracetamol, zopiclone and tramadol. Investigation of telephone enquiries to the New Zealand National Poisons Centre showed total poisoning calls increased slightly over the 10 year period, whereas telephone enquiries from hospitals halved. Conclusion: The TOXINZ Internet accessible poisons information database has proved to be a well‐utilised addition to the New Zealand National Poisons Centre's service.